MGMT in glial carcinogenesis. Roles from prevention to treatment. Issue 6 (3rd June 2022) - Elmaci, İlhan; Altinoz, Meric A.; Kahraman Ozlu, Eylem Burcu; Sari, Ramazan; Er, Ozlem; Gokhan Ekmekci, Cumhur; Turkgenc, Burcu; Ozpinar, Alp; Hacker, Emily; Ozpinar, Aysel
Abstract : Many investigations exist regarding the effect of the DNA repair enzyme MGMT (O 6 -methylguanine- DNA-methyltransferase)-encoding gene methylation on the antineoplasticity of temozolomide in glioblastoma patients. However, there exist surprisingly lesser studies regarding the associations between MGMT enzyme biochemistry with glial carcinogenesis. MGMT involves in risk of malignancies associated with ionizing radiation, smoking, exposure to polycyclic aromatic hydrocarbons, chlorinated solvents, vinylchloride and hairdyes. All these factors are also proposed to link with gliomagenesis, yet MGMT interactions with these carcinogens in gliomagenesis are not studied yet. In future, MGMT sequencing may be employed in vulnerable populations working in industries associated with exposure to these carcinogens to develop preventive strategies. Given that MGMT is involved in DNA repair, a polymorphism may simultaneously modify the risk of gliomas while enhancing temozolomide cytotoxicity in both marrow and tumor cells.